Promotion and Investments in Family Farming for Food and Nutritional Security - Nain, M. S.; Singh, Rashmi; Sharma, J. P. (Indian Farming, 2015)
To implement the vision of IYFF the global line of action has been outlined in three statements viz; Promotion of dialogue in policy decision-making processes; Identification, documentation and sharing lessons learned and successful experiences of existing pro-family farming policies at national and/or other levels to capitalize relevant knowledge on family farming and Communication, advocacy and outreach.